Peaks and valleys: oscillatory cerebral blood flow at high altitude protects cerebral tissue oxygenation. (29th June 2021) - Anderson, Garen K; Rosenberg, Alexander J; Barnes, Haley J; Bird, Jordan; Pentz, Brandon; Byman, Britta R M; Jendzjowsky, Nicholas; Wilson, Richard J A; Day, Trevor A; Rickards, Caroline A
Abstract: Introduction. Oscillatory patterns in arterial pressure and blood flow (at ∼0.1 Hz) may protect tissue oxygenation during conditions of reduced cerebral perfusion and/or hypoxia. We hypothesized that inducing oscillations in arterial pressure and cerebral blood flow at 0.1 Hz would protect cerebral blood flow and cerebral tissue oxygen saturation during exposure to a combination of simulated hemorrhage and sustained hypobaric hypoxia. Methods. Eight healthy human subjects (4 male, 4 female; 30.1 ± 7.6 year) participated in two experiments at high altitude (White Mountain, California, USA; altitude, 3800 m) following rapid ascent and 5–7 d of acclimatization: (1) static lower body negative pressure (LBNP, control condition) was used to induce central hypovolemia by reducing chamber pressure to −60 mmHg for 10 min (0 Hz), and; (2) oscillatory LBNP where chamber pressure was reduced to −60 mmHg, then oscillated every 5 s between −30 mmHg and −90 mmHg for 10 min (0.1 Hz) . Measurements included arterial pressure, internal carotid artery (ICA) blood flow, middle cerebral artery velocity (MCAv), and cerebral tissue oxygen saturation (ScO2 ). Results. Forced 0.1 Hz oscillations in mean arterial pressure and mean MCAv were accompanied by a protection of ScO2 (0.1 Hz: −0.67% ± 1.0%; 0 Hz: −4.07% ± 2.0%; P  = 0.01). However, the 0.1 Hz profile did not protect against reductions in ICA blood flow (0.1 Hz: −32.5% ± 4.5%; 0 Hz: −19.9% ± 8.9%; P  = 0.24) or mean MCAv (0.1 Hz: −18.5% ± 3.4%; 0 Hz: −15.3% ± 5.4%; P  = 0.16). Conclusions. Induced oscillatory arterial pressure and cerebral blood flow led to protection of ScO2 during combined simulated hemorrhage and sustained hypoxia. This protection was not associated with the preservation of cerebral blood flow suggesting preservation of ScO2 may be due to mechanisms occurring within the microvasculature.